PENGARUH IKLAN DAN PENYELENGGARAAN EVENT DI KLENTENG SAM POO KONG TERHADAP KEPUASAN PENGUNJUNG MELALUI KEPUTUSAN BERKUNJUNG (Studi pada Pengunjung Klenteng Sam Poo Kong) - Risky Shintia Diliani; Widayanto Widayanto (Universitas Diponegoro, 2020)
The tourism sector has great potential in supporting the country's economy. The growth of visitors in the city of Semarang continues to experience growth of visitors in the city of Semarang continues to experience growth so that encourage the creation of new tourist destinations and increase tourism competition. Klenteng Sam Poo Kong is one of the tourist destinations in Semarang City which is the oldest Chinese temple in Semarang. Klenteng Sam Poo Kong is unique in its architectural style of buildings full of Chinese nuances and there is the highest Cheng Ho statue in the world, besides being a tourist destination it can also be used as a place of worship. This type of research is explanatory research, using a questionnaire as a method of data collection. The purpose of this study was to determine the direct effect between the variable Advertising and Organizing Event on Visitor Satisfaction, and the indirect effect of Advertising and Organizing Event on Visitor Satisfaction through a Visiting Decision on Visitors to the Klenteng Sam Poo Kong. The research method used is the Non Probability Sampling technique with the Purposive Sampling method. Samples collected as many as 100 respondents were visitors to the Klenteng Sam Poo Kong which were chosen based on consideration. The study uses a Partial Least Square analysis technique, which is estimated by the WarpPLS 6.0 program. Based on the analysis of data processing with WarpPLS explained that the test results of direct and indirect effects on the research model showed positive and significant results. The researcher gave advised to the manager of the Klenteng Sam Poo Kong based on the lowest recapitulation value given by respondents to the assessment indicators, namely doing ad serving during breaks and at after work hours, improving the quality of the performers' performance such as adding barongsai dance attractions on poles and adding dragon dance, continuing to improve the quality of service, performance, and facilities needed and desired by visitors, so that the sacrifice of time and energy that has been spent by visitors is commensurate with those obtained during the visit, and includes information both writing or photos that are by the reality at the tourist attractions so that respondents' expectations are in line with or exceed ith what was found during a visit.